A Spheroid Model of Early and Late-Stage Osteosarcoma Mimicking the Divergent Relationship between Tumor Elimination and Bone Regeneration - Freeman, Fiona; Kelly, Daniel (My University, 2021)
Osteosarcoma is the most diagnosed bone tumor in children. The use of tissue engineering strategies after malignant tumor resection remains a subject of scientific controversy. As a result, there is limited research that focuses on bone regeneration postresection, which is further compromised following chemotherapy. This study aims to develop the first co-culture spheroid model for osteosarcoma, to understand the divergent relationship between tumor elimination and bone regeneration. By manipulating the ratio of stromal to osteosarcoma cells the modelled cancer state (early/late) is modified, as is evident by the increased tumor growth rates and an upregulation of a panel of well-established osteosarcoma prognostic genes. Validation of the authors' model is conducted by analyzing its ability to mimic the cytotoxic effects of the FDA-approved chemotherapeutic Doxorubicin. Next, the model is used to investigate what effect osteogenic supplements have, if any, on tumor growth. When their model is treated with osteogenic supplements, there is a stimulatory effect on the surrounding stromal cells. However, when treated with chemotherapeutics this stimulatory effect is significantly diminished. Together, the results of this study present a novel multicellular model of osteosarcoma and provide a unique platform for screening potential therapeutic options for osteosarcoma before conducting in vivo experiments.
PUBLISHED
Keywords: Osteosarcoma; Biological Models; Cellular Spheroids; Growth Factors; Chemotherapies; Bone Regeneration; Cancer; BONE REGENERATION; OSTEOSARCOMA